Desenvolvimento e validação de métodos rápidos para analises de resíduos de fármacos e pesticidas em matrizes biológicas e vegetais por LC-MS/MS - Freitas, Diego Ruiz de (Universidade Federal de São Carlos, 2014)
The increased demand for chemical analysis and the growing concern with the environment implies in the urgency for more modern analytical methods of extraction and analysis to be developed and validated, seeking a significant reduction in solvent consumption and analysis time. In the present work it was purpose to make use of modern, cheaper and faster sample extraction techniques, as well as chromatographic system based on ultrafast chromatograph systems (UHPLC), using columns packet with reduced diameter of particles that enable to reduce significantly the time of analysis, solvent consumption and reagents, and coupling with mass spectrometry (LC-MS/MS). All developed methods were fully validated according to the RDC 27/2012 and the RDC 04/2012 in the case of pesticides. All results are within the parameters required for each standard validation. An average 50% reduction in analytical costs, increasing profitability, and the productive capacity of laboratories with the reduction of materials and analysis time where achieved.
Development and validation of fast methods for analysis of residual drugs and pesticides in biological and vegetables samples by LC-MS/MS
Keywords: Resíduos; Espectrometria de massas; Validação do método; CIENCIAS EXATAS E DA TERRA::QUIMICA